THE DIFFERENCES IN TROPONIN I AND CK-MB VALUES IN ACUTE MYOCARDIAL INFARCTION PATIENTS WITH ST ELEVATION AND WITHOUT ST ELEVATION - Paulus Rio Kurniawan; Andreas Arie Setiawan; Charles Limantoro; Ariosta Ariosta (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Acute myocardial infarction includes STEMI and NSTEMI. In STEMI and NSTEMI, an increase in cardiac biomarkers especially troponin I and CK-MB are affected by the ischemic process. In STEMI thrombus blocks the entire artery lumen while in NSTEMI thrombus does not block the entire artery lumen. This can lead to different ischemic processes. Aim: To prove the differences in troponin I and CK-MB values in acute myocardial infarction patients with ST-elevation and without ST- elevation. Methods: An observational analytic study using a cross-sectional design was conducted between April and September 2020. The total sample of the study was 48 samples, consists of 25 samples with STEMI and 23 samples with NSTEMI. The normality test was analyzed using Shapiro-Wilk test. The difference test was analyzed using Mann-Whitney test. Results: Mean troponin I values of STEMI and NSTEMI patients were 30.40 ± 20.79 ng/mL; 1.38 ± 1.76 ng/mL, respectively. Mean CK-MB values in STEMI and NSTEMI patients were 386.12 ± 319.70 U/L; 42.39 ± 27.54 U/L, respectively. There were statistically significant differences in troponin I and CK-MB values (p respectively 0.00; 0.00) in STEMI patients compared to NSTEMI patients. Conclusion: There were differences in troponin I and CK-MB values between STEMI and NSTEMI patients. The troponin I and CK-MB values in STEMI patients were higher than in NSTEMI patients.